Operating room nurses' lived experiences of ethical codes: A phenomenological study in Iran - Fateme Aghamohammadi; Behzad Imani; Mahnaz Moghadari Koosha (Elsevier, 2021)
Objective: Operating room nurses, as essential members of health care teams, often face ethical challenges in the operating room. By using the ethical experiences of operating room nurses, a better understanding of ethics in the operating room can be achieved, which can lead to better nursing decisions in the face of these challenges. Therefore, this study was conducted to investigate operating room nurses' lived experiences of ethical codes. Methods: A hermeneutic phenomenological study was performed in Hamadan (Iran) from February 2019 to November 2020. Ten operating room nurses were selected as participants by purposive sampling. Data were collected through in-depth and semi-structured interviews. Data analysis was performed based on Van Manen methodology. Results: Data analysis revealed three main themes and 11 sub-themes representing the operating room nurses experience of the ethical code. The main themes were; adherence to professional commitments, preserving patient dignity, and respect to colleagues. Conclusion: The results underlined ethics and ethical values in the operating room. Due to the intense interactions between operating room nurses with the patient and surgical team, commitment to ethics by nurses can lead to improving quality of care and interactions among members of the surgical team. It is suggested that using these codes as a guideline and a framework could be developed to improve the ethical and professional performance of operating room nurses.